2016
DOI: 10.3758/s13420-016-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

Bigger brains may make better problem-solving carnivores

Abstract: ) recent demonstration that larger-brained carnivores were more successful in a single problem-solving task, relative to smaller-brained carnivores, irrespective of social complexity, poses a challenge to proponents of the social intelligence hypothesis (Humphrey, 1976) and provides some support for the idea that larger relative brain sizes have evolved to support greater problem-solving abilities. However, an important question, neglected by the authors, is the extent to which foraging ecology, rather than so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Tests of the social complexity hypothesis for communication have used a variety of different definitions of social complexity. Some authors have suggested that group size is a reasonable index of social complexity (Street, Navarrete, Reader, & Laland, 2017; Vonk, 2016; Zimmermann, 2017), with the caveat that the group is not considered “social” if it is a simple aggregation around some resource (e.g., food or water) or forms due to some short-term external stimulus (e.g., predators). At the least, there should be some level of individual (Roberts & Roberts, 2016; Sewall, 2015) or group (Boughman & Wilkinson, 1998; Price, 1999; Tyack, 2008; Yurk, Barrett-Lennard, Ford, & Matkin, 2002) recognition that would facilitate stable social relationships among group members.…”
Section: Communicative Social and Cognitive Complexitymentioning
confidence: 99%
“…Tests of the social complexity hypothesis for communication have used a variety of different definitions of social complexity. Some authors have suggested that group size is a reasonable index of social complexity (Street, Navarrete, Reader, & Laland, 2017; Vonk, 2016; Zimmermann, 2017), with the caveat that the group is not considered “social” if it is a simple aggregation around some resource (e.g., food or water) or forms due to some short-term external stimulus (e.g., predators). At the least, there should be some level of individual (Roberts & Roberts, 2016; Sewall, 2015) or group (Boughman & Wilkinson, 1998; Price, 1999; Tyack, 2008; Yurk, Barrett-Lennard, Ford, & Matkin, 2002) recognition that would facilitate stable social relationships among group members.…”
Section: Communicative Social and Cognitive Complexitymentioning
confidence: 99%
“…However, similar to the MacLean et al (2014) study, there was little evidence for the importance of social group size or complexity. In future, it will be important to investigate the role of dietary factors in predicting success of carnivores in solving foraging related extraction problems and to present animals with more than a single task to assess ability (Vonk 2016). Sol and colleagues (Sol et al 2005) have examined the role of brain size in a more naturalistic assessment of intelligence.…”
Section: Assessments In Nonhumansmentioning
confidence: 99%
“…A number of hypotheses aiming to explain the evolution of brain size variation among and within different vertebrate taxa have been formulated (Isler & van Schaik, 2009; Kotrschal et al ., 2019; Sol, 2009). On one side the cognitive buffer hypothesis (CBH; Sol, 2009) predicts that large relative brain masses (to body size) are associated with increased cognitive abilities with the potential to enhance the efficiency of behavioural responses to novel socio‐ecological challenges (González‐Lagos et al ., 2010; Sol, 2009; Vonk, 2016), such as rapid reactions to unexpected threats ( e.g ., avoiding predation), finding new food sources or obtaining a mate (Allman et al ., 1993; Benson‐Amram et al ., 2016; Holekamp & Benson‐Amram, 2017; Striedter, 2005). On the other side, however, the metabolic costs associated with the development of larger brains have to be met by either increasing the total energy budget ( e.g ., by increasing foraging time) or compensating for changes through energy allocation to other maintenance or developmental functions, as predicted by the expensive brain framework (EBF; Isler & van Schaik, 2009).…”
Section: Introductionmentioning
confidence: 99%